Hypoglycemia While Driving in Insulin-Treated Patients: Incidence and Risk Factors - Lohan, Laura; Clément, Florian; Duflos, Claire; Villiet, Maxime; Castet-Nicolas, Audrey; Boegner, Catherine; Avignon, Antoine; Sultan, Ariane; Breuker, Cyril (Journal of patient safety, 2021)
This study aimed to investigate a potential daily-life concern for patients with diabetes hypoglycemia while driving by (1) estimating their incidence in insulin-treated drivers, (2) determining factors associated with their occurrence, and (3) analyzing patients' behavior regarding prevention of hypoglycemia. We conducted an observational study from November 2013 to May 2018 in the endocrinology-diabetology-nutrition department of our university hospital. All patients treated for diabetes older than 18 years admitted in the department were eligible. A specific questionnaire assessing attitudes, knowledge, and consequences of hypoglycemia was provided. In this study, only insulin-treated patients who regularly drive were analyzed. On the 233 insulin-treated drivers included, 45 (19%) self-reported at least 1 hypoglycemia while driving in the preceding year. Two factors were significantly associated with their occurrence: type 1 diabetes (odds ratio [OR] = 3.19; 95% confidence interval [CI] = 1.55-6.57) and experiences of asymptomatic hypoglycemia (OR = 2.20; 95% CI = 1.05-4.63). Awareness of the treatment hypoglycemia risk because of information provided by a medical specialist was also but nonsignificantly associated with hypoglycemia while driving (OR = 2.61; 95% CI = 0.86-7.92). Forty-one patients (18%) combined those 3 variables, 20 (49%) of them self-reported hypoglycemia while driving. Thirty-four percent of the patients never carried carbohydrates for hypoglycemia correction. Seventy-six percent do not monitor blood glucose level before driving. Our questionnaire allowed us to highlight that 19% our cohort of insulin-treated drivers declared experiencing hypoglycemia while driving. Risk factors identified and prevention data collected should help us better target patient education.